2005
DOI: 10.1111/j.1469-8137.2005.01401.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity profiling of ectomycorrhiza communities in two forest soils using multiple enzymatic tests

Abstract: Summary• Data on the diversity and distribution of enzyme activities in native ectomycorrhizal (ECM) communities are inadequate.• A microplate multiple enzymatic test was developed which makes it possible to measure eight enzyme activities on 14 individual, excised ECM root tips. Hydrolytic and oxidative enzymes are involved in the decomposition of lignocellulose, chitin and phosphorus-containing organic compounds. This test system was used to describe the functional diversity of ECM communities in two forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
176
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 220 publications
(185 citation statements)
references
References 23 publications
(41 reference statements)
7
176
2
Order By: Relevance
“…Experimental site of Champenoux Fourteen ECM tips of each morphotype (chosen among the most turgid and healthy-looking ones, from a pooled sample of those of the six soil cores in which this ECM type was present) were used to determine their potential enzymatic activities, using the high-throughput photometric and fluorimetric microplate assays described by Pritsch et al (2004) and Courty et al (2005), and applied in previous studies (Buée et al 2007). Each well of the 96-well micro-titration plate contained a single ECM tip.…”
Section: Enzymatic Activity Profiling Of Ecmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental site of Champenoux Fourteen ECM tips of each morphotype (chosen among the most turgid and healthy-looking ones, from a pooled sample of those of the six soil cores in which this ECM type was present) were used to determine their potential enzymatic activities, using the high-throughput photometric and fluorimetric microplate assays described by Pritsch et al (2004) and Courty et al (2005), and applied in previous studies (Buée et al 2007). Each well of the 96-well micro-titration plate contained a single ECM tip.…”
Section: Enzymatic Activity Profiling Of Ecmsmentioning
confidence: 99%
“…Activities of extracellular enzymes can be considered as functional traits to study functional diversity and resilience of ectomycorrhizal community (Cullings and Courty 2009). The first applications of this novel approach (e.g., Courty et al 2005Courty et al , 2007Buée et al 2007;Rineau and Garbaye 2009b;Jones et al 2010) have revealed that the activity profile of ECMs formed by the same species may change significantly according to everchanging ecological conditions (i.e., seasons, short-term climatic events, tree phenology, accidental or man-made disturbances such as soil amendment).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on their substrate, the enzymes can be phosphomonoesterases or phosphodiesterases. Most of the studies addressing the release of phosphatases use artificial phosphomonesters such as p-nitrophenyl phosphate (pNPP) based on the procedure described in Tabatabai and Bremner (1969) or the fluorescent assay based on the release of 4-methylumbelliferone from 4-methylumbelliferonephosphate (MUP; Courty et al 2005Courty et al , 2006Pritsch et al 2004;Pritsch and Garbaye 2011) to estimate phosphomonoesterase activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far, most of the ECM fungi showed maximal activities of released or surfacebound phosphomonoesterase at acidic pH when assayed with pNPP (Tibbett 2002) or with MUP (Courty et al 2005). ALP was measured in cell extracts of Cenococcum graniforme (renamed Cenococcum geophilum), and although the enzyme showed a high association with cell wall material, it was not released into the external medium from young fungal cultures (Bae and Barton 1989).…”
Section: Introductionmentioning
confidence: 99%